Anticipation resulting in elimination of the myotonic dystrophy gene: a follow up study of one extended family. Issue 8 (August 1994) - de Die-Smulders, C E; Höweler, C J; Mirandolle, J F; Brunner, H G; Hovers, V; Brüggenwirth, H; Smeets, H J; Geraedts, J P
Abstract : We have re-examined an extended myotonic dystrophy (DM) family, previously described in 1955, in order to study the long term effects of anticipation in DM and in particular the implications for families affected by this disease. This follow up study provides data on 35 gene carriers and 46 asymptomatic at risk family members in five generations. Clinical anticipation, defined as the cascade of mild, adult, childhood, or congenital disease in subsequent generations, appeared to be a relentless process, occurring in all affected branches of the family. The cascade was found to proceed asynchronously in the different branches, mainly because of an unequal number of generations with mild disease. The transition from the mild to the adult type was associated with transmission through a male parent. Stable transmission of the asymptomatic/mild phenotype showed a female transmission bias. We further examined the extent and causes of gene loss in this pedigree. Gene loss in the patient group was complete, owing to infertility of the male patients with adult onset disease and the fact that mentally retarded patients did not procreate. Out of the 46 at risk subjects in the two youngest generations, only one was found to have a full mutation. This is the only subject who may transmit the gene to the sixth generation. No protomutation carriers were found in the fourth and fifth generations. Therefore it is highly probable that the DM gene will be eliminated from this pedigree within one generation. The high population frequency of DM can at present not be explained by the contribution of asymptomatic cases in the younger generations of known families, but is probably caused by the events in the ancestral generations.